Respostas
respondido por:
2
Boa noite Angelica
a)
x² - 3x = 0
x*(x - 3) = 0
x1 = 0
x2 = 3
b)
3x² + 15x = 0
x² + 3x = 0
x*(x + 3) = 0
x1 = 0
x2 = -3
c)
2x² - 10x = 0
x² - 5x = 0
x*(x - 5) = 0
x1 = 0
x2 = 5
a)
x² - 3x = 0
x*(x - 3) = 0
x1 = 0
x2 = 3
b)
3x² + 15x = 0
x² + 3x = 0
x*(x + 3) = 0
x1 = 0
x2 = -3
c)
2x² - 10x = 0
x² - 5x = 0
x*(x - 5) = 0
x1 = 0
x2 = 5
Angelicaimperial:
Boa noite obrigada viu
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás